How is motivation located in the instructional design process? - Sanal, Seda Özer (IGI Global, 2021)
Instructional design is used to design and carry out effective learning processes, based on the dynamics of human learning. So, what we know about learning is very important. The chapter aims to reveal the position of a concept closely related to learning in instructional design. The concept of motivation is too comprehensive and complex to be limited to the learning domain. With a broad perspective, it can be defined as the willingness of human to life and everything in life. Motivation is also closely related to many important elements such as energy, effort, desire, interest, goal, satisfaction, continuity. And these concepts are actually items related to learning and instructional design. However, effective and efficient learning will take place with motivated learners and other parameters realized. The fact that motivation is such a widespread component of life, especially having a critical role in the teaching process, made the authors question its place in the teaching design process. © 2021, IGI Global.